SURVEY ON CHALLENGES OF ONLINE TEACHING AND LEARNING FOR INTERACTIVE MULTIMEDIA SUBJECT DURING COVID-19 PANDEMIC - Nur Idawati Md Enzai; Mohd Amir Hamzah Ab Ghani; Siti Sara Rais (Journal of Islamic, Social, Economics and Development, 2022)
The unprecedented global pandemic had really impacted all aspects of life includingeducation. Online teaching and learning which used to be the alternative method has beenquickly deployed due to schools and universities being closed. As a result, many problemsemerged such as technological and emotional well-being issues. This paper addresses thetechnological issue by conducting a survey among 48 UiTM students enrolled in Diploma Hoteland Tourist Management who take Interactive Multimedia subject. The survey explores theperceptions of students regarding software installation and usage issues. The students’concerns include difficulty to install software and device does not support the software. Theinstructor’s view was also obtained and the possible remedies to the challenges are alsopresented.